LIMITATIONS OF FINANCIAL AND OPERATING RATIOS. - Paton, W. A. (The Accounting Review, 1928)
Abstract The use of financial and operating ratios as a means of rendering accounting statements more intelligible and significant is a matter which deserves the consideration it has been receiving of late. This device certainly represents an important angle from which the problem of statement presentation and analysis can be approached and is worthy of every encouragement. And it is a thoroughly natural and appropriate device for the accountant to emphasize. In fact any system of accounts may be conceived as a set-up of business data in terms of their underlying relations. It is clear, accordingly, that in presenting final statements and reports the accountant must not be satisfied that his work is complete with the compilation of masses of debits and credits. Through classification and arrangement, charts and graphs, oral and written explanations, or other means he must see to it that all important relationships are disclosed and this means of course that all significant financial and operating percentages must be calculated and exhibited. On the other hand, the enthusiasm for ratios as such seems at times to go beyond reasonable bounds. What one has here after all is a very commonplace feature of accounting work, long recognized and used and no great good can come from exaggerating its significance and scope.